Analysis of the current state program INNOVATION SUBJECTS OF THE RUSSIAN FEDERATION - M. Abramova; S. Manakhov (Вестник университета)
The paper shows and gives justification to the definition «program» which wasn't used earlier in case of state planned economy of the Soviet period, and legislatively snugged at the moment within an economical and managerial profile as a complex of the interconnected projects and actions united by a common goal and coordinated jointly for the purpose of increase in general effectiveness and controllability. In the course of transition of Russia from system of central planning to fundamentals of market economy denial of the plan was observed, and the program became the instrument of state regulation of national economy. In article the analysis of programs as package of measures concerning innovative development of economy of Russia is carried out.